Analysis Implementation The Appointment Village Officials From Siyasah Tanfidziyah Perspective In Gedung Jaya Village - Tri Saputra, Adi Tiya; Frenki, Frenki; Hendriyadi (Fakultas Syariah INSURI Ponorogo, 2025)
This study aims to analyze the impact of the appointment mechanism for village officials that does not comply with Tulang Bawang Regent Regulation No. 10 of 2020 concerning Guidelines for the Appointment of Village Officials, with a focus on the case in Gedung Jaya Village, Rawa Pitu District, Tulang Bawang Regency. This field research uses observation, interviews, and documentation methods to identify the legal implications and community response to the village apparatus appointment process. Field findings indicate that procedural irregularities, including the absence of open selection and administrative transparency, have the potential to infringe upon community rights and undermine the stability of village governance. From a siyasah tanfidziyah perspective, this mechanism has essentially adopted the principles of musawah (equality), tolerance, freedom, justice ('adl), syura (consultation), and compliance with sharia law; however, its implementation has not been effective in creating optimal social harmony and justice. The results of this study emphasize the importance of enforcing regional regulations, increasing accountability, and strengthening the integration of siyasah tanfidziyah values in public administration to achieve a village governance system that is fair, stable, and in the best interests of the community.